Analysis of water quality of selected irrigation water sources in northern Ghana - Kadyampakeni, Davie; Appoh, Richard K.; Barron, Jennie; Boakye-Acheampong, Enoch (IWA Publishing, 2018)
Small-scale irrigation continues to cushion the food security gap in sub-Saharan Africa. Irrigation is largely governed by water availability, soil type and crop water requirements, among other factors. Thus, a study was conducted to assess the suitability of various water sources for irrigation in northern Ghana. Specifically, the study sought to assess quality of water sources in the Savelugu, Kasena-Nankana East, and Nabdam districts for small-scale irrigation development. The water quality parameters used were: pH, electrical conductivity (ECw), sodium adsorption ratio (SAR), sodium percent (Na%), soluble sodium percentage (SSP), magnesium adsorption ratio (MAR), Kelley's ratio (KR), total hardness (TH), Chloride (Cl), E. coli, and Faecal coliforms. While we found most of the irrigation water sources, including small reservoirs, dams, wells and rivers suitable, few unsuitable irrigation water sources were also identified. Overall, the study found that opportunities for scaling small-scale irrigation exist in all the sites. The knowledge generated from this study will guide irrigation water use, and agricultural policy for sustainable smallholder irrigation development in the region.